Isolation and Characterization of Potential Isolates of Rhizosphere Bacteria to Contro Budok Disease in Patchouli Plant - NFN Sukamto; Novi Listiana; Reni Indrayanti; Dono Wahyuno (Buletin Penelitian Tanaman Rempah dan Obat, 2019)
Synchytrium pogostemonis, the causal agent of budok disease, is one of the major limiting factors in patchouli production in Indonesia. Patchouli farmers usually control budok disease with chemical fungicides. Chemical control pollutes environment and disrupts agricultural ecosystem. Therefore, an environmentally friendly pest control should be conducted to control the disease. The objective of the study was to isolate and evaluate some rhizobacteria from the rhizosphere of patchouli and black pepper plants against Fusarium oxysporum f.sp. vanillae, F. solani, Sclerotium rolfsii. Potential rhizobacterial isolates were tested to control budok disease on a pot scale. The results showed that 26 rhizobacterial isolates from 100 tested were antagonistic to F. oxysporum, F. solani and S. rolfsii. Four rhizobacteria isolates (RL13-A, RL31-A, RL35-A, RL32-A) showed strong inhibition (>40 %) against the 3 pathogens. In polibag experiment, RL35-A, PS9, RL13-A, RL32-B, RL31-A isolates were able to suppress budok disease significantly by 84.01; 76.00; 65.99; 43.99; and 21.98 % respectively. These results indicated that RL35-A isolates have strong antagonistic effect compared to other isolates. Based on 16S rDNA analysis, RL35-A isolates possessed close relationship (99 %) with all species of Enterobacter sp. The antibiotic compound extracted from RL35-A culture broth using GC-MS analysis was identified as phenol, 2,6-dimethoxy-(canola). These results suggested that Enterobacter sp. was potential to be developed as biological agent for controlling budok disease in patchouli plants.